Research and Implementation of High-Efficiency and Low-Complexity LDPC Coding Algorithm - Liao, Xiong; Guo, Junxiong; Luo, Zhenghua; Xu, Yanghui; Chu, Yingjun (Electronics (Basel), 2023)
In this work, we proposed a high-efficiency and low-complexity encoding algorithm and its corresponding implementation structure during the design and implementation process of an LDPC encoder and decoder. This proposal was derived from extensive research on and analysis of standard encoding algorithms and recursive iterative encoding algorithms, specifically targeting the problem of high computational complexity in encoding algorithms. Subsequently, we combined binary phase-shift keying modulation mode and additive white Gaussian noise channel transmission with the min-sum decoding algorithm to realize the (1536, 1024) LDPC codec. This codec was uniformly quantized with a (6, 2) configuration, executed eight iterations, and achieved a 2/3 code rate in the IEEE802.16e standard. At the bit error rate (BER) of 10−5, the codec’s BER obtained by the proposed coding algorithm was about 0.25 dB lower than the recursive-iterative coding algorithm and was about 1.25 dB lower than the standard coding algorithm, which confirms the correctness, effectiveness, and feasibility of the proposed algorithm.